2005
DOI: 10.1200/jco.2005.14.167
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of an Oral Histone Deacetylase Inhibitor, Suberoylanilide Hydroxamic Acid, in Patients With Advanced Cancer

Abstract: Purpose-To determine the safety, dosing schedules, pharmacokinetic profile, and biologic effect of orally administered histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) in patients with advanced cancer.Patients and Methods-Patients with solid and hematologic malignancies were treated with oral SAHA administered once or twice a day on a continuous basis or twice daily for 3 consecutive days per week. Pharmacokinetic profile and bioavailibity of oral SAHA were determined. Western blots and enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
826
4
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 981 publications
(867 citation statements)
references
References 18 publications
35
826
4
2
Order By: Relevance
“…Similarly, TSA which is associated with excessive toxicity and is unstable in vivo has limited clinical applicability (Jung, 2001;Hess-Stumpp, 2005). However, other hydroxamic acid derivatives including SAHA and pyroxamide have completed phase I trials and are progressing further in clinical trials (Kelly et al, 2002(Kelly et al, , 2003Kelly and Marks, 2005). Results from phase I trials have shown that intravenous SAHA formulations are safe and can inhibit HDAC activity in malignant and normal cells (Kelly et al, 2002(Kelly et al, , 2003Kelly and Marks, 2005).…”
Section: Cellular Effects Of Hdac Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, TSA which is associated with excessive toxicity and is unstable in vivo has limited clinical applicability (Jung, 2001;Hess-Stumpp, 2005). However, other hydroxamic acid derivatives including SAHA and pyroxamide have completed phase I trials and are progressing further in clinical trials (Kelly et al, 2002(Kelly et al, , 2003Kelly and Marks, 2005). Results from phase I trials have shown that intravenous SAHA formulations are safe and can inhibit HDAC activity in malignant and normal cells (Kelly et al, 2002(Kelly et al, , 2003Kelly and Marks, 2005).…”
Section: Cellular Effects Of Hdac Inhibitorsmentioning
confidence: 99%
“…However, other hydroxamic acid derivatives including SAHA and pyroxamide have completed phase I trials and are progressing further in clinical trials (Kelly et al, 2002(Kelly et al, , 2003Kelly and Marks, 2005). Results from phase I trials have shown that intravenous SAHA formulations are safe and can inhibit HDAC activity in malignant and normal cells (Kelly et al, 2002(Kelly et al, , 2003Kelly and Marks, 2005). Importantly, SAHA was shown to possess anticancer activity in a broad range of hematologic and solid cancers.…”
Section: Cellular Effects Of Hdac Inhibitorsmentioning
confidence: 99%
“…Indeed, chemical inhibitors of HDACs have been shown to inhibit tumor cell growth and induce differentiation and cell death. [5] Several such inhibitory agents, including suberoyanilide hydroxamic acid (SAHA, aka virinostat) and depsipeptide (FR901228) have reached clinical trials, [6][7][8] and SAHA has been approved by the FDA for use in cutaneous T-cell lymphoma (CTCL). The HDAC inhibitors (HDACIs) also enhance the cytotoxic effects of both radiation and chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The reversible nature of epigenetic changes in cancer cells by inhibitory agents has been explored as a new avenue for cancer treatment. Histone deacetylase (HDAC) inhibitors were recently found to be well-tolerated in patients with hematologic and solid malignancies [17]. Several classes of HDAC inhibitors exist, and they display diverse effects on cellular functions.…”
Section: Introductionmentioning
confidence: 99%